Effect of Reflexology on Anxiety Level in Nuliparous Women - F Mirzaee; M Kaviani; P Jafari (Tehran University of Medical Sciences, 2010)
Background & Objective: Labor potentially causes stress and anxiety, especially in nulliparous women. In Iran, many pregnant women undergo cesarean section electively due to fear of labor pain. The purpose of this study was to investigate the effect of reflexology on the anxiety level, blood pressure, and pulse in nulliparous women in Kerman.Methods & Materials: In this clinical trial, 70 nulliparous women with gestational age more than 37 weeks and cervical dilatation of 3-4 cm were recruited for the study. The participants were randomly allocated to two equal reflexology and control groups. The reflexology group received the intervention for 20 minutes (each foot: 10 minutes) on their feet and the control group received massage for 20 minutes on their legs. Anxiety level, blood pressure and pulse rate were measured at baseline and immediately after the intervention using Spielberger questionnaire.Results: Anxiety level did not differ between the two groups at baseline (P=0.85). After the intervention, the mean of anxiety level was significantly lower in the reflexology group than in the control one (P<0.001). The pulse rate (P=0.44) and blood pressure (P=0.59) did not differ significantly in two study groups after the intervention.Conclusion: Reflexology reduced anxiety level in labor.